Persiapan Kembali Ke Sekolah / Amelie Lamirand; penerjemah, Shelomi Angeli ; editor, Widya Ayu, Windrati Hapsari - LAMIRAND, Amelie; Windarti Hapsari; Shelomi Angeli; Widya Ayu (Erlangga, 2014)
23 hlm. : ilus. ; 22 cm.